Effect of Bio-Cementation on the Strength Characteristics of Compacted Lateritic Soil Under Sterilized and Unsterilized Conditions - Gadzama, E. W.; Eberemu, A. O.; Ijimdiya, T. S.; Osinubi, K. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Naturally, not all soils readily meet specifications for engineering use. Therefore, improvement of soil engineering properties is one of the main concerns of a civil engineer. This paper evaluates the strength characteristics of a deficient lateritic soil classified as an A-4(3) using the American Association of State Highway and Transportation Officials (AASHTO) classification system and CL using the Unified Soil Classification system (USCS) after improvement, using microbial induced calcite precipitation (MICP) technique. The soil sample was obtained from a site in Abagana, in Anambra State. It was treated with varying suspension densities up to 2.40 x 109 cells/ml of Sporosarcina pasteurii (S. pasteurii) a non-pathogenic microorganism cultured from the soil, under sterilized and unsterilized condition. The treated soil was compacted using the British Standard Light (Standard Proctor) compactive effort at the moulding water content range of -2 to +4% optimum moisture content (OMC). The compacted soil specimens were then permeated a cementitious reagent containing 20 g of Urea, 10 g of NH4Cl, 3 g of Nutrient broth, 2.8 g of CaCl2 and 2.12 g of NaHCO3 per litre of de-ionized water to aid the microbial induced calcite precipitation (MICP) process in three circles with 2/3rd pore volume. The Atterberg limits results showed a better improvement in the sterilized than the unsterilized specimens. Similarly, the unconfined compressive strength generally recorded higher results in the unsterilized specimens. Highest unconfined compressive strength (UCS) results were recorded at S. pasteurii suspension densities of 1.20 x 109 /ml and 1.80 x 109 /ml for the unsterilized and sterilized specimens respectively. Microstructural analysis using X-ray Diffraction performed on precipitates derived through the interaction of S. pasteurii and the cementitious reagent confirmed calcite as the dominant composition of the precipitate, analysis using the scanning electron microscopy (SEM) on the MICP treated soil depicts presence of calcite precipitate and bio-cementation on the surface morphology of the treated soil grains. It was concluded that there are other species of microorganisms that augmented the MICP processes in the unsterilized specimens resulting to higher UCS values in the study. 1.20 x 109 /ml S. pasteurii suspension density was recommended as the optimal mix for the treatment of the unsterilized soil.